Diction in the Lyrics of the Song Ngilmu Pring by Jogja Hiphop Foundation: A Stylistic Study - Kurnianingrum, Aprilia; Sulanjari, Bambang (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2024)
The purpose of this study was to determine the use of diction and its function in the lyrics of the song Ngilmu Pring by the Jogja Hiphop Foundation. This study used descriptive qualitative method. The research data are in the form of phrases, words, and sentences in the lyrics of the song Ngilmu Pring by the Jogja Hiphop Foundation. Data collection techniques used in this study used inventory, read-listening, and recording techniques.